Simulation and Application Purpose of a Randomized Secret Key with Quantum Key Distribution - Grote, Olaf; Ahrens, Andreas (Electrical, Control and Communication Engineering, 2022)
The Quantum Key Distribution (QKD) is a well-researched secure communication method for exchanging cryptographic keys only known by the shared participants. The vulnerable problem of a secret key distribution is the negotiation and the transfer over an insecure or untrusted channel. Novel further developments of the QKD communication method are part of in-field technologies and applications in communication devices, such as satellites. However, expensive physical test setups are necessary to improve new application possibilities of cryptographic protocol involving components of quantum mechanics and quantum laws of physics. Therefore, optical simulation software can play a part in essential QKD simulating and further developing quantum-based cryptosystems. In the paper, the authors consider a feasible QKD setup based on the BB84 protocol to create a symmetric key material based on achieving a linear key rate via optical simulation software. The paper still provides two experimental architecture designs to use the QKD for a cryptosystem.